The Influence of Financial Performance and Political Connections on Stock Returns Transportation and Logistics Companies Going Public on the IDX (2021-2023) - Wyne Carolina; Khairudin (Cita konsultindo, 2026)
Shares are also proof of return of shares or participants in a company in the form of a PT (Limited Liability Company). Finding empirical evidence regarding the influence of financial performance and political connections on stock returns is the aim of this research. This research was conducted quantitatively using a sample of transportation and logistics companies going public on the IDX (2021-2023). The analytical method used is multiple linear analysis. Simultaneously, the research results show that the variables ROA, CR and Political Connections have an effect on Stock Returns, but partially ROA and CR have an effect and Political Connections have no effect on Stock Returns.